Gut microbiota and functional outcome after ischemic stroke: a Mendelian randomization study - Qu, Dian; Jiang, Deming; Xin, Yan; Yang, Guichun; Liang, Huan; Wang, Linlin (Frontiers in Immunology, 2024)
Background: Previous studies have shown that gut microbiota dysbiosis may affect the clinical prognosis through unknown mechanism. However, the causal relationship between gut microbiota and functional outcome after ischemic stroke remains unclear. We aim to investigate causal association between gut microbiota and functional outcome after ischemic stroke using Mendelian randomization (MR). Methods: Genetic instrumental variables associated with 211 bacterial traits were obtained from MiBioGen consortium (N = 18,340). GWAS data for functional outcome after ischemic stroke was obtained from two phenotypes (overall stroke outcome and motor recovery). The inverse variance weighted method was used to estimate the causal association. Enrichment analysis was conducted base on the results of MR analyses. Results: Genetically predicted family Peptostreptococcaceae (OR = 0.63; 95% CI = 0.41–0.98; P = 0.038), genus LachnospiraceaeNK4A136 group (OR = 0.65; 95% CI = 0.43–1.00; P = 0.048), genus LachnospiraceaeUCG004 (OR = 0.54; 95% CI = 0.33–0.90; P = 0.017), and genus Odoribacter (OR = 0.40; 95% CI = 0.21–0.77; P = 0.006) presented a suggestive association with favorable functional outcome, while genus Eubacterium oxidoreducens group (OR = 1.77; 95% CI = 1.11–2.84; P = 0.018) and genus RuminococcaceaeUCG005 (OR = 1.85; 95% CI = 1.15–2.96; P = 0.010) were associated with unfavorable functional outcome. Genetically predicted family Oxalobacteraceae (OR = 2.12; 95% CI = 1.10–4.11; P = 0.025) and genus RuminococcaceaeUCG014 (OR = 4.17; 95% CI = 1.29–13.52; P = 0.017) showed a suggestive association with motor recovery, while order Enterobacteriales (OR = 0.14; 95% CI = 0.02–0.87; P = 0.035) and family Enterobacteriaceae (OR = 0.14; 95% CI = 0.02–0.87; P = 0.035) were associated with motor weakness. Enrichment analysis revealed that regulation of synapse structure or activity may be involved in the effect of gut microbiota on functional outcome after ischemic stroke. Conclusions: This study provides genetic support that gut microbiota, especially those associated with short-chain fatty acids, may affect stroke prognosis by mediating synapse function. Our findings suggest that modifying the composition of gut microbiota may improve the prognosis of ischemic stroke.